Humoral Response and Safety after a Fourth Dose of the SARS-CoV-2 BNT162b2 Vaccine in Cancer Patients Undergoing Active Treatment—Results of a Prospective Observational Study - Chiara Citterio; Claudia Biasini; Camilla Di Nunzio; Giuliana Lo Cascio; Luigi Cavanna (Vaccines, 2024)
Only a few studies have been carried out on the efficacy and safety of a fourth dose of the COVID-19 vaccine in patients with cancer. In this prospective observational study, we aimed to assess the serological response and safety of the fourth booster shot of the BNT162b2 vaccine in 79 cancer patients, vaccinated between 1 March and 25 August 2022, under systemic anticancer therapy. The primary endpoint was to assess the increase in the anti-SARS-CoV-2 antibodies; secondary endpoints were the vaccine safety and side effects. Consequently, 40 patients (50.63%) revealed the maximum detection values in their IgG titers before the fourth dose of the vaccine, while 39 patients (49.37%) did not. Primary endpoint: Of 39 patients, 36 (92.31%) showed a significant increase in the anti-SARS-CoV-2 IgG titers, and 32 of them (82.05%) reached the maximum titration values. Secondary endpoints: The most common adverse events were mild in severity and included injection site pain, erythema and tiredness. The majority of the adverse reactions reported were grade 1 and no grade 3 and 4 reactions were detected. Our data provide evidence that a fourth dose of the BNT162b2 anti-SARS-CoV-2 vaccine is effective and safe in patients with solid tumors in active anticancer treatment.